Lessons from Grenfell: Poverty propaganda, stigma and class power. Issue 4 (July 2018) - Shildrick, Tracy
The Grenfell Tower fire that took place in a council owned high-rise housing block in the early hours of 14 June 2017 in the London Borough of Kensington and Chelsea represented the worst fire in Britain for many decades. This article draws, in part, on the example of Grenfell Tower to interrogate some of the most pressing issues of our time around poverty, inequality and austerity. After a period of quiet, poverty now features more regularly in popular and political conversations. This is, in part, due to the proliferation of foodbanks that in many ways have become the public face of poverty in contemporary Britain. Additionally the increased popularity of so-called 'poverty porn' exemplified by programmes such as Benefit Street have provoked public and political debate about the realities of poverty and its causes and consequences. Punitive policies towards out of work benefits claimants, austerity measures and the proliferation of low paid and insecure work mean poverty has been extended to more and more people, yet at the same time it is a condition that is frequently stigmatised, misrepresented and misunderstood. Whilst evidence shows increased stereotyping and stigmatisation of those experiencing poverty and other related disadvantages, there is also evidence that the British general public on the whole tend to care about fairness, equality of opportunity and that they dislike extremes of income and wealth, although importantly they also generally underestimate the realities of both. It was these extremes of inequality that Grenfell thrust so violently into the public imagination with many newspapers visually capturing the gulf between rich and 'poor' in their pictures of the burnt out shell of Grenfell set against a typical block of luxury apartments of the sort that are proliferating in London and other cities in Britain and that, particularly in London, often cost in excess of a million pounds or more. This article looks at examples of how critical work is being done by those in power to manipulate and frame the terms of the discussion around poverty, inequality and economic insecurity and its causes and its consequences.